Design and characterization of VHF band small antenna using CRLH transmission line and non-foster matching circuit - Lee, Soyeong; Lee, Jonghyup; Choi, Seongro; Lee, Yong Hyeok; Chung, Jae Young; Hwang, Keum Cheol; Park, Yong Bae (Applied Sciences (Switzerland), 2020)
In this paper, we propose an electrically small antenna consisting of a composite right/left-handed (CRLH) transmission line (TL) and a non-Foster matching circuit. An interdigital capacitor (IDC) and spiral inductor are used to fabricate the very high frequency (VHF) band antenna based on CRLH TL. The size of the proposed antenna is as small as 0.025 × 0.014 × 0.0008 λ at 145.5 MHz using the zeroth-order resonant generated by the CRLH TL. The antenna operation bandwidth is extended by the non-Foster circuit (NFC) consisting of a pair of transistors in a cross-coupled manner. An antenna prototype is fabricated and the input impedance, the received power, and gain of the proposed antenna are measured. The results show that the broadband characteristic is maintained while the form factor is extremely small compared to the wavelength. The average received power enhancement and increased bandwidth of antenna are 17.3 dB and 335.5 MHz (from 249.2-268.2 to 145.5-500 MHz), respectively. The calculated gain of the proposed antenna with the non-Foster is about -45 dBi at 155 MHz. The proposed antenna can be considered as a potential candidate of a low-profile antenna for military ground communications at the VHF band.
Keywords: Composite right/left-handed transmission lines; Military antenna; Non-foster circuit; VHF band antenna